Aerial robot swarms: a review - Luthra, Manan (IAES International Journal of Robotics and Automation (IJRA), 2023)
The purpose of this review is to highlight the current research on aerial robot swarms and their applications. It focuses on the system architecture and follows the current trend in aerial robotics promoting research in this field along with its impact on society. Further, it explores the dynamics as well as the flying mechanisms of a drone and sheds light on the different algorithms being used to control aerial swarms. Due to a lot of research going on in this field, we also discuss the different trends that are active and of keen interest to the researchers, including the swarm pattern formation behavior.